Understanding The Concept Of Pythagoras In Junior High School Students Using PMRI - Ariani, Sinta; Widyaningrum, Indah; Rahayu, Chika (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
This research aims to determine students' conceptual understanding using the PMRI learning approach with the context of cotton rope in the Pythagorean theorem material on students' conceptual understanding in class VIII SMP NEGERI 2 Pagaralam. The obstacle faced by students in studying the Pythagorean Theorem is a lack of understanding of the basic concepts in the Pythagorean theorem material. One method that can strengthen understanding of concepts in learning mathematics is Indonesian Realistic Mathematics Education (PMRI). The research method used was experimental using a control group Pre-test - Post-test design. This research involved 2 classes, namely the experimental and control classes. Data collection techniques include observation and tests, the analysis techniques used are documentation, observation and tests. Based on test data analysis, the average student score in the experimental class was 78.8, while the control class had a score of 72.50. From the research results, students' conceptual understanding was found to be better using PMRI with comparison results in the experimental class being better than in the control class.